Drivers of conservation and utilization of pineapple genetic resources in Benin - Achigan-Dako, Enoch G.; Adje, C.A.; N'Danikou, Sognigbe; Fassinou-Hotegnim N.V.; Agbangla, C.; Ahanchédé, A. (Springer, 2014)
Valuation of farmer knowledge has been seen as a route to promote sustainable use of plant genetic resources. In pineapple production systems in Benin, inadequate knowledge of cultivation practices can lead to a number of inconveniences including abandon of some varieties and cultivars. To understand how farmers' knowledge and cultivation practices impact the sustainable utilization of pineapple genetic resources, we surveyed 177 pineapple farmers in southern Benin. We assessed farmers' knowledge and analyzed the relationship between their knowledge and factors such as age, education, and locality of provenance. Pineapple production system was dominated by men (96% respondents). According to farmers, Smooth cayenne is international market-oriented while Sugarloaf mainly targets domestic and regional markets. All farmers recognized that Smooth cayenne provided more income (USD 5,750/ha) than sugarloaf (USD 3,950/ha) in the production systems of southern Benin. The high value of median scores in comparison with the range of possible score showed that most farmers agreed and shared relatively similar knowledge. Correlation matrix and multiple linear regressions showed a significant relationship between farmers'practices and their knowledge of the plant; their knowledge of pineapple varieties is based on fruits traits. Also, farmers' knowledge was associated with locality of provenance. Constraints and options for genetic resources conservation and utilization in the pineapple production systems in Southern Benin were discussed based on current knowledge